ANALISIS KINERJA PENGGILINGAN PADI PADA BERBAGAI SKALA USAHA STUDI KASUS DI KECAMATAN BUAY MADANG TIMUR KABUPATEN OKU TIMUR PROVINSI SUMATERA SELATAN - Putri, Ayu Sang; Rosanti, Novi; Saleh, Yuliana (Lampung University, 2024)
This research aims to analyze the process of procuring raw materials and the performance of rice mills at different business scales in East Buay Madang District. This research used a case study method on rice mills with different business scales in East Buay Madang District, East OKU Regency, South Sumatra. The rice mill owner was the respondent in this research. Data collection was carried out from March to April 2021. The data analysis method used was descriptive qualitative and quantitative analysis. The results showed that the procurement of raw materials for rice mills at different business scales was not appropriate because there were several components that are not optimal. The performance of rice mills in East Buay Madang District is not yet optimum, because one the four production performance indicators, which is indicator of capacity at small scale rice mills, still needs to be enhanced to be more optimum. .Key words: business scale, performance, procurement, rice mill